2004
DOI: 10.1074/jbc.m308496200
|View full text |Cite
|
Sign up to set email alerts
|

Unzipping the Role of Myosin Light Chain Phosphatase in Smooth Muscle Cell Relaxation

Abstract: MBS isoforms could explain differences in tissue sensitivity to NO-mediated vasodilatation.Force regulation in smooth muscle is dependent on the activities of myosin light chain (MLC) 1 kinase and MLC phosphatase (3, 4). The activity of MLC kinase is regulated by Ca 2ϩ -calmodulin (3), whereas MLC phosphatase was originally thought to be constitutively active and unregulated (5). However, there is abundant evidence that the activity of MLC phosphatase can be both inhibited to produce Ca 2ϩ sensitization (revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
94
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 31 publications
9
94
0
Order By: Relevance
“…Four MYPT1 fragments (Fig. 1A) were subcloned from the full-length chicken aorta MYPT1 cDNA (13,23,24). The production of four endogenous MYPT1 isoforms depends on the presence or absence of a CI and a downstream LZ (12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four MYPT1 fragments (Fig. 1A) were subcloned from the full-length chicken aorta MYPT1 cDNA (13,23,24). The production of four endogenous MYPT1 isoforms depends on the presence or absence of a CI and a downstream LZ (12).…”
Section: Methodsmentioning
confidence: 99%
“…Studies with glutathione S-transferase (GST)-fusion peptides have demonstrated that the NH 2 -terminal LZ of PKGI␣ (24) and COOH-terminal LZ of MYPT1 (23) are important for the PKGI␣-MYPT1 interaction. However, using full-length MYPT1, we have demonstrated that although the LZ domain is important for cGMP-mediated activation of MLC phosphatase, it may not mediate the binding of PKGI␣ to MYPT1 (13). Therefore, the MYPT1-PKGI␣ interaction may depend on the presence of an upstream domain.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…9 In vitro and in vivo evidence showed that the LZ motif present in the C-terminal of MYPT1 is required for the activation of MP by type I PKG. [10][11][12] The sensitivity of smooth muscle to cGMP/PKG-mediated relaxation is proportional to the expression ratio of LZ þ / LZ À MYPT1. [10][11][12] In smooth muscle cells, the relationship between MP activity and the phosphorylation of MYPT1 has been extensively studied.…”
mentioning
confidence: 99%
“…[10][11][12] The sensitivity of smooth muscle to cGMP/PKG-mediated relaxation is proportional to the expression ratio of LZ þ / LZ À MYPT1. [10][11][12] In smooth muscle cells, the relationship between MP activity and the phosphorylation of MYPT1 has been extensively studied. 13 However, changes in MYPT1 abundance have only been reported by a few studies.…”
mentioning
confidence: 99%